2015
DOI: 10.1039/c4tb01515k
|View full text |Cite
|
Sign up to set email alerts
|

In vivo analysis of the size- and time-dependent uptake of NaYF4:Yb,Er upconversion nanocrystals by pumpkin seedlings

Abstract: We have investigated the kinetics of the uptake and the translocation of nanoparticles of different size in plants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
34
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 48 publications
0
34
0
Order By: Relevance
“…Haase and co-workers performed the in vivo analysis of sizeand time-dependent uptake of NaYF 4 :Yb,Er@NaGF 4 UCNPs by pumpkin seedlings. 435 It was found that the UCNP accumulation took place eventually in the leaf margin ( Figure 39b,c). The uptake of smaller UCNPs was faster than that of larger UCNPs, leading to higher concentrations of smaller UCNPs at early times of incubation.…”
Section: Upconversion Nanoparticles For Bioimagingmentioning
confidence: 97%
“…Haase and co-workers performed the in vivo analysis of sizeand time-dependent uptake of NaYF 4 :Yb,Er@NaGF 4 UCNPs by pumpkin seedlings. 435 It was found that the UCNP accumulation took place eventually in the leaf margin ( Figure 39b,c). The uptake of smaller UCNPs was faster than that of larger UCNPs, leading to higher concentrations of smaller UCNPs at early times of incubation.…”
Section: Upconversion Nanoparticles For Bioimagingmentioning
confidence: 97%
“…Up to now, some works pertaining to the short‐term/subchronic/long‐term toxicities, biodistribution, and excretion behavior of UCNPs in live organisms such as nude mouse and Caenorhabditis elegans have been reported . However, reports on the toxicities and the interactions of UCNPs with plants are scarce . As an important component of the environment, plants play a significant role in preserving the ecological system equilibrium and can provide one of the main food sources of animals and human beings .…”
Section: Introductionmentioning
confidence: 99%
“…The appropriate functionalization of the NP surface and the introduction of targeting molecules such as folic acid, some peptides, specific antibodies and growth factors permits in some cases a cellular targeting imaging [263][264][265]. In vivo luminescent bioimaging of bacteria [266,267], small animals (mostly mice) [268,269] and plants [262,270] with UCNPs has also been widely reported in the literature. Different processes of biomedical interest can be also studied in vivo by using UCNPs, as it is the case of the biodistribution of the NPs [271] and targeting [272][273][274][275].…”
Section: Upconverting Nanophosphors For Luminescent Bioimagingmentioning
confidence: 99%